Peran Penyuluh dalam Keberhasilan Kelompok Peternak Sapi Potong di Kecamatan Tabongo, Kabupaten Gorontalo - Minarsi Tihua; Widiastuti Ardiansyah; Susan Mokoolang; Ishak Korompot (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the role of extension agents in supporting the success of beef cattle farmer groups in Tabongo District, Gorontalo Regency. The success of farmer groups is influenced not only by livestock potential, but also by the effectiveness of extension services, institutional capacity, and farmers’ willingness to adopt improved farming practices. Using an explanatory approach, the study collected primary data from 50 members of beef cattle farmer groups across nine villages through a Likert-scale questionnaire. Data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression. The descriptive findings show that extension agents performed well as educators, facilitators, motivators, dynamizers, and catalysts. However, the catalyst role was excluded from the regression model because its indicators were invalid. Partially, only the motivator role had a significant effect on group success, with a coefficient of 1.683, t-value of 4.758, and significance value of 0.000. The educator, facilitator, and dynamizer roles showed positive but insignificant effects. Simultaneously, the roles of extension agents significantly influenced group success, with an F-value of 9.474 and significance value of 0.000. The R Square value of 0.457 indicates that extension agents explained 45.7% of group success.